Design Of Microstrip Bandpass Filter With Electronically Tunable Notch Response - Mohamad Ariffin, Mutalib; Zahriladha, Zakaria; Noor Azwan, Shairi; Sam, Weng Yik (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
An integrated high selectivity microstrip wideband bandpass filter with tunable notch response is presented in this paper. The bandpass filter is designed using 7th order short circuited stub filter. Then, the first short circuited stub is replaced with two sections of open circuited stub to exhibit the transmission zeros at lower/higher stopband. The integration with notch filter is realized using U-shape Defected Microstrip Structure (DMS) with varactor diode. By properly varying the DC bias voltages, the notch response can be tuned over a constant bandwidth of around 17%. The experimental result shows that the bandwidth of the wideband bandpass filter is between 2.9 GHz – 5.8 GHz. The notch’s tuning range from 4 GHz to 5 GHz is achieved using varactor diode respectively. This type of filter is suitable for applications such as the multi-service and multiband communication system in order to discriminate the undesired signals.